2016
DOI: 10.1097/gox.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Perioperative Antibiotic Dosing and Surgical Site Infection Rate in Office-Based Elective Surgery

Abstract: Background:A best practice goal to reduce surgical site infection includes administration of antibiotics in the ideal preoperative window. This article evaluates an office surgical suite antibiotic administration rate and compares it with the timing of a local hospital treating a similar patient population. The hypothesis was that similar or better compliance and surgical site infection rates can be achieved in the office-based suite.Methods:A total of 277 office-based surgeries were analyzed for antibiotic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We have already extensively studied and published on infection control in breast tissue. 32 , 33 Of course, the breast case becomes inherently colonized over the course of the surgical procedure; however, the sources of the infectious agents are the nipple ducts and axilla, not the instruments. We have found no evidence in the literature to suggest that changing instruments leads to a decrease in surgical site infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…We have already extensively studied and published on infection control in breast tissue. 32 , 33 Of course, the breast case becomes inherently colonized over the course of the surgical procedure; however, the sources of the infectious agents are the nipple ducts and axilla, not the instruments. We have found no evidence in the literature to suggest that changing instruments leads to a decrease in surgical site infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative phase Pain management planning—acute narcotic prescription medications are provided, appropriate to the severity of anticipated postoperative pain, with the expectation of prompt transitioning to OTC/non-opioids 70-73 Limited preoperative fasting, as per ASA 2016 Task Force Guidelines 85 Preoperative anxiolytics—gabapentin 86 1-2 hours prior, SSI prevention No shaving, clipping hair 87-92 immediately preoperative Preoperative hibicleanse showers 93 Preoperative nasal mupirocin 94 Single dose IV antibiotic prophylaxis, given 0-60 minutes prior to incision 54,95,96 Preoperative synergy: Clonidine 0.25 mg p.o 97 Immediately preoperative: Benadryl, supplemental oxygen, hydration, and phenergan. …”
Section: Eras Bl Protocolmentioning
confidence: 99%
“…SSI prevention No shaving, clipping hair 87-92 immediately preoperative Preoperative hibicleanse showers 93 Preoperative nasal mupirocin 94 Single dose IV antibiotic prophylaxis, given 0-60 minutes prior to incision 54,95,96 …”
Section: Eras Bl Protocolmentioning
confidence: 99%
“…A meta-analysis by Stijn et al, demonstrated the importance of timing of administration (30–60 minutes prior to incision time), selection of agent for specific microbes (narrow spectrum antibiotics) and duration of prophylaxis (single pre-operative dose or intraoperative re-dosing if indicated) in prevention of SSI [ 2 ]. Unfortunately, non-compliance to guidelines is still observed and prolonged use of antibiotics leads to an increase in SSI rates and increased antimicrobial resistance rates [ 3 5 ]. An antimicrobial resistance situation analysis in 2015 in Tanzania indicated the resistance of Streptococcis pnemoniae to Trimethoprim and Sulphamethoxazole had increased from 25% in 2006 to 80% in 2012.…”
Section: Introductionmentioning
confidence: 99%